Analysis of the Effectiveness of the Literacy-Orientation-Collaboration-Reflection (LOC-R) Learning Model in Science Learning Activities of Islamic Elementary School Students - Iskandar, Suhendra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Unlike other learning models, the LOC-R learning model focuses on literacy in learning material so that no single learning objective is neglected. However, the learning concept still relies on student-centered learning (SCL). This research examined the effectiveness of the LOC-R learning model (literacy, orientation, collaboration, and reflection) in science learning activities for Madrasah Ibtidaiyah Teacher Education IAIN Sultan Amai Gorontalo students. The research used a learning model focusing only on lecturers' lectures and a learning model concentrating on students' independent presentations as a control group. Three learning materials were selected for the science learning activities, two for the control group (one-way lecture and presentation) and one for the test group, assessed as having the same difficulty level. The success of learning activities is evaluated in two aspects: learning outcomes and student interest in learning. To test the learning outcomes of each group, a pre-test was carried out at the beginning of each learning activity and a post-test at the end of each learning activity for the three groups. Then, the results were analyzed using the N-gain test technique. In addition, a semi-quantitative analysis of students' learning interests was also carried out through questionnaires. The results obtained were that the LOC-R learning model was proven to improve student learning outcomes as seen from the N-gain value of 87.4035%, which was much greater than the control group, where the one-way lecture method only produced an N-gain value of 39.5127% and the presentation method produced an N-gain value of 45.6645%. However, based on the questionnaire given to students who took the LOC-R learning model test, not all showed positive interest, with 50% of students rating it positively, 13.64% rating it neutral, and 36.36% rating it negatively. From this research, researchers can conclude that the LOC-R learning model has proven effective in improving student learning outcomes. However, there is still a need to think about ways to package the learning model innovatively so that it can be popular with all students.